ANALISIS BISNIS DIGITAL (SKEMA PONZI DAN SKEMA PIRAMIDA) DI ERA REVOLUSI INDUSTRI 4.0 BAGI MASYARAKAT DI KABUPATEN KOTABARU BERDASARKAN UU NO. 8 TAHUN 1995 TENTANG PASAR MODAL DAN UU NO. 7 TAHUN 2014 TENTANG PERDAGANGAN - Grenada Floren (KINDAI, 2021)
Abstract: The ignorance of the people, especially those living in Kotabaru Regency regarding the existence and implementation of Law no. 08 of 1995 concerning the capital market and Law no. 7 of 2014 concerning trade, is used by illegal business actors to implement Ponzi schemes, pyramid schemes and insider trading on the businesses they offer. This study aims to find out about the development of digital business in the industrial revolution era, the implementation of Law no. 8 of 1995 concerning the capital market and Law no. 7 of 2014 concerning Trade in digital business, providing knowledge in choosing the right and appropriate digital business products. The sampling technique used was Quota sampling which was carried out on 50 respondents spread over 6 Districts in Kotabaru Regency. The qualitative descriptive analysis technique uses the scoring results from the questionnaire, for the results of the questionnaire with negative indications, further observations are carried out using purposive/judgmental techniques. From the results of the research, it was found that there are still many people who are entangled in illegal businesses. Keywords: Ponzi Scheme, Pyramid Scheme, Law No. 8 of 1995 concerning Markets Capital and Law no. 7 of 2014 concerning Trade Abstrak : Ketidaktauan masyarakat khususnya yang tinggal di Kabupaten Kotabaru mengenai keberadaan dan pengimplementasian UU No. 08 Tahun 1995 tentang pasar modal dan UU No. 7 Tahun 2014 tentang perdagangan, dimanfaatkan oleh oknum pelaku bisnis ilegal untuk menerapkan skema Ponzi, skema piramida dan insider trading pada bisnis yang mereka tawarkan. Penelitian ini bertujuan untuk mengetahui mengenai perkembangan bisnis digital pada era revolusi industri, implementasi UU No. 8 Tahun 1995 Tentang pasar modal dan UU No. 7 Tahun 2014 Tentang Perdagangan pada bisnis digital, memberikan pengetahuan dalam memilih produk bisnis digital tepat dan sesuai. Teknik pengambilan sampel menggunakan Quota sampling yang dilakukan pada 50 orang responden yang tersebar pada 6 Kecamatan di Kabupaten Kotabaru. Teknik analisis deskriptif kualitatif menggunakan hasil skoring dari kusioner, untuk hasil kuisioner berindikasi negatife di lakukan pengamatan lanjutan menggunakan teknik purposive/judgmental. Dari hasil penelitan di temukan masih banyak masyarakat yang terjerat dalam bisnis ilegal. Kata Kunci : Skema Ponzi, Skema Piramida, UU No.8 Tahun 1995 Tentang Pasar Modal dan UU No. 7 Tahun 2014 Tentang Perdagangan